Experimental investigation on the influence of sub- and super-critical CO2 saturation time on the permeability of fractured shale. (15th January 2020) - Zhou, Junping; Tian, Shifeng; Zhou, Lei; Xian, Xuefu; Yang, Kang; Jiang, Yongdong; Zhang, Chengpeng; Guo, Yaowen
Abstract: The permeability variation of shale due to the CO2 saturation induced deformation has significant influence on the overall CO2 injection capacity and shale gas production. In this study, the effect of subcritical (SubCO2 ) and supercritical CO2 (ScCO2 ) saturation and its action time on the permeability evolution of fractured shale sample was examined. Five saturation times (4, 10, 12, 18, 24 h), both for SubCO2 (6 MPa) and ScCO2 (8 MPa), were introduced to the shale sample. For each saturation cyclic, the permeability of shale sample was determined by helium injection with various injection pressures (2–6 MPa). Results indicated that the permeability of shale sample is significantly reduced after CO2 saturation, and is decreased with the increase of CO2 saturation time due to the time dependent adsorption-induced swelling. ScCO2 induced a higher permeability reduction and a longer permeability reduction process than SubCO2, due to its higher affinity and higher viscosity in shale. The permeability has a negative exponential relation with effective stress for SubCO2 and ScCO2 saturated shale samples. After CO2 saturation, the stress sensitivity of shale permeability increased with the CO2 saturation time, which is related to the time dependent mechanical weakening of shale induced by CO2 -shale interaction. ScCO2 induced a larger increase in stress sensitivity of shale permeability than SubCO2, because it induced more remarkable weakening of mechanical properties in shale. Highlights: The permeability of shale decrease with the increase of SubCO2 and ScCO2 saturation times. ScCO2 induced more permeability reductions and longer reduction processes than SubCO2 . Permeability has a negative exponential relation with effective stress for CO2 saturated shale. The stress sensitivity of permeability in shale is increased with CO2 saturation time. ScCO2 induced a larger increase in stress sensitivity of shale permeability than SubCO2 .